A Novel Method to Identify Important Edges in a Directed Network - Saiyu Yuan; Wenqiang Liu; Guanghui Yan; Hongwu Tang; Xing Cheng (Axioms)
Identifying the key components in complex systems is crucial for ensuring the functionality and integrity of the system. For directed networks, both nodes and edges are critical components, but little attention has been drawn to the important edges. In this paper, a novel method, Cooperation–Competition Centrality (Co-Com Centrality), has been proposed to quantify the edge importance in a directed network. This method utilizes cooperation and competition relationships to integrate the local and global information about the network. We compare the performance of Co-Com Centrality with five typical methods in nine networks; the experiments show that Co-Com Centrality can accurately identify edges which are crucial for maintaining global network efficiency and network stability, while also accurately assessing the edge importance.